2003
DOI: 10.1002/ajmg.b.20013
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of the association between the catecholamine‐O‐methyl‐transferase gene and obsessive‐compulsive disorder

Abstract: Obsessive-compulsive disorder (OCD) is a chronic, severely debilitating mental illness that affects approximately 1-2% of the population. Data from twin and family studies have shown that genetic factors contribute to the expression of the disease. The dopaminergic system has been implicated in the pathogenesis of OCD, and catecholamine-O-methyl-transferase (COMT) is a key modulator of dopaminergic and noradrenergic neurotransmission. The gene for COMT has a common polymorphism that has been shown to be correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 23 publications
2
36
0
4
Order By: Relevance
“…It has also been strongly associated with one anxiety disorder in particularFpanic disorder ( (Ohara et al, 1998;Samochowiec et al, 2004) and, according to a recent meta-analysis, not with obsessive-compulsive disorder (Azzam and Mathews, 2003). There was therefore ample a priori reason to hypothesize that we would find an effect of the val158met polymorphism on neuroticism and extraversion in this study.…”
Section: Discussionmentioning
confidence: 57%
“…It has also been strongly associated with one anxiety disorder in particularFpanic disorder ( (Ohara et al, 1998;Samochowiec et al, 2004) and, according to a recent meta-analysis, not with obsessive-compulsive disorder (Azzam and Mathews, 2003). There was therefore ample a priori reason to hypothesize that we would find an effect of the val158met polymorphism on neuroticism and extraversion in this study.…”
Section: Discussionmentioning
confidence: 57%
“…[31][32][33] As such, the candidacy of COMT as a susceptibility gene for OCD is relatively, perhaps unexpectedly, strong, and has substantially advanced since the equivocal positive result of the earlier meta-analysis, which was based on 144 OCD cases and 337 controls. 34 In terms of mechanism, an involvement of COMT in OCD likely reflects its role in modulation of cortical dopamine metabolism, although its role in methylation of other substrates, including catecholestrogens, should be noted. 2 We assume that the association of the met 158 allele with OCD reflects the lower enzyme activity of met-COMT 12 and the consequent enhancement of cortical dopamine signalling, relative to val-COMT.…”
Section: Discussionmentioning
confidence: 99%
“…For example, whereas some studies have reported a link between the COMT met allele and increased predisposition to clinical anxiety and heightened subclinical anxiety levels, others have failed to do so (Azzam & Mathews, 2003;Ohara, Nagai, Suzuki, Ochiai, & Ohara, 1998). This is likely to reflect the complexity of the mechanisms and associated genetic influences involved.…”
Section: Discussionmentioning
confidence: 99%